2018
DOI: 10.1016/s0140-6736(18)30485-9
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus in patients with clinically active systemic lupus erythematosus resistant to, or intolerant of, conventional medications: a single-arm, open-label, phase 1/2 trial

Abstract: Pfizer, the National Institutes of Health, and the Central New York Community Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
245
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 328 publications
(257 citation statements)
references
References 41 publications
12
245
0
Order By: Relevance
“…Metabolic reprogramming is cell type-specific; for example, pDC activation by type I IFN relying on FAO instead of glycolysis [61], a process that has not been found in other types of DCs. Furthermore, mTOR inhibitors and metformin show promising results in SLE [25,30]. In addition, some metabolites such as succinate or itaconate show previously unsuspected anti-inflammatory effects [122].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metabolic reprogramming is cell type-specific; for example, pDC activation by type I IFN relying on FAO instead of glycolysis [61], a process that has not been found in other types of DCs. Furthermore, mTOR inhibitors and metformin show promising results in SLE [25,30]. In addition, some metabolites such as succinate or itaconate show previously unsuspected anti-inflammatory effects [122].…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of immune cells is already targeted by a drug commonly used by rheumatologists, methotrexate, which interferes with 1-Carbon metabolism [124]. Furthermore, mTOR inhibitors and metformin show promising results in SLE [25,30]. It would also be of great interest to explore the metabolic consequences of current treatments used or tested by rheumatologists to have a clearer understanding of the mechanisms by which drugs or biologics modulate the immune system effectively or not through altered metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lupus and Sjogren's syndrome occur when mTOR is activated, and its blockade with rapamycin is therapeutically effective [70]. Recent investigations have demonstrated that both mTOR and rapamycin have pivotal roles of antiaging, development, various diseases such as cancer, diabetes, obesity and also tissue injury [71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%